Synthesis of carbon nanotubes (CNTs) using supported catalysts - Tee, Jia Chee; Buang, Nor Aziah; Sanip, Suhaila M.; Ismail, Ahmad Fauzi (2004)
Catalytic properties of cobalt (Co), fermm (Fe) and mixture of cobalt and fermm (Co- Fe) supported on aluminium oxides (AI2O3) and molecular sieves (MS) have been investigated in the synthesis of carbon nanotubes (CNTs). The supported catalysts were prepared by impregnation method. The supports were impregnated with metal salt solutions of Co, Fe or mixture of Co and Fe so as to gct spccific wcight percentage of thc metal on the supports. Acetylene is used as the source of carbon in inert condition. The pyrolysis of acetylene was carried out at temperature 700 OC. The effects of types of supports and catalyst. quantity of catalyst as well as the calcination process have also been studied. Types of Co or Fe metal compound formed on the support and the effect of calcination were determined by X-ray diffraction technique (XRD) and energy dispersive X-ray analysis (EDAX). Scanning electron microscope (SEM) and EDAX was used to study the quality and nature of as-grown CNTs. Results obtained showed that CNTs with different diameter sizes and form were produced from these types of supported catalysts.